Peran Kepolisian Resor Kota Besar Makassar Dalam Menangani Kasus Kekerasan Dalam Rumah Tangga Di Kota Makassar - Munawara, Munawara; Muhammadiyah, Muhammadiyah; Ma'ruf, Adnan (Universitas Muhammadiyah Makassar, 2020)
This study aimed to describe how the role of the Makassar big city police in handling cases of domestic violence in the city of Makassar. This study used descriptive qualitative method. The number of informants in this study were 6 people. The results of this study showed that the aspect of communication carried out by the police, it run well through social media, the community and victims who got violence, the educational aspect was the police did socialization into the community to provide counseling. Aspects of socialization carried out by police by collaborating with the village government to share the PKDRT law to the community. Apart from the village government there were also community shelters formed by integrated services centers of women and children and directly sheltered by the Office of Women’s Empowerment and City Child Protection Makassar. And the aspect of advocacy aimed to provide understanding related to domestic violence in community.